Le Nôtre, un ancêtre encombrant ? Variations autour de l’enseignement de l’histoire dans la formation des architectes-paysagistes versaillais (1873-1945) - Stéphanie de Courtois (Projets de Paysage)
When Édouard André described teaching at the École d'horticulture de Versailles in 1890, the course on garden and greenhouse architecture given by Auguste Choisy included a laconic "summary history of gardens" which provided a short introduction to the main objective of the course: training in the technique of garden composition. However, before 1945, most practical garden treatises included history among their subject matters. After the renewal of the school of landscape architecture under the direction of Adolphe Alphand, at a time when nationalist sentiment took the figure of Le Nôtre as a reference and cities conducted their redevelopment based on the Cornudet law, the question of history took on greater significance: How did it interact with social sciences and geography? The article explores the successive ways in which history was acculturated to landscape architecture at the Versailles school of landscape architecture by the five teachers who taught the discipline. Why take an interest in history and what does the landscape architect seek to find in it: inspiring places, techniques, solutions for building perspectives, a repository of forms, and the ability to understand the history of a place? This article describes a stage in the formulation of these questions which are still relevant.